Mortality for neurological diseases and pesticides: etiological hypotheses by a spatial analysis in the province of Pavia - Ferraro, Ottavia Eleonora; Guido, Davide; Zambianchi, Roberto; Lanfranchi, Simone; Oddone, Enrico; Villani, Simona (La Medicina del Lavoro, 2018)
Background: Neurological and neurodegenerative diseases are multifactorial and their causes are not well understood yet. Among the relevant risk factors, pesticides and the productive activities in which they are used are included. Objectives: To evaluate the association of mortality from neurological diseases within the Province of Pavia (Italy) with the agricultural activities, as a proxy of pesticides exposure. Methods: Population data for 2012 were provided by the local health unit (ATS) and by the registry office of the Regional Health Service. Spatial analyses were carried out by both a classical and Bayesian approach, to obtain a mortality map of the relative risk for neurological diseases in the Province of Pavia. Spatial distribution of main agricultural activities within the same territory, used as proxy of pesticides use, was made possible by data from the Geoportale Territoriale of the Lombardy region. Finally, a comparison between spatial distribution of mortality from neurological diseases and spatial distribution of main agricultural activities has been conducted. Results: Mortality for neurological diseases in the Province of Pavia in 2012 was 4.41 for men and  6.53 for women per 10,000 subjects living in this area. Female mortality for neurological diseases showed a cluster in the Oltrepò district, where viticulture and fruit/horticulture are more common than elsewhere. More precisely, Bayesian relative risk (RR) had higher values in comparison with the median RR of the Province (100.8), with a posterior probability (PP) between 0.75 and 0.95 (not significant). Similarly, mortality for Parkinson’s disease in women showed RR greater than the median value of the Province (100.6), with PP between 0.25 and 0.75 (not significant). Conclusions: Notwithstanding the ecological nature of the study, our results suggest the need to further investigate the possible link between pesticides exposure or related activities and neurological and neurodegenerative diseases, particularly Parkinson’s disease. An ad hoc study on a random sample of the population living in the Province of Pavia, with the collection of individual data by means of standardized questionnaire, would allow to control for biases usually present when an ecological study design is applied.